2021
DOI: 10.3389/fimmu.2021.664576
|View full text |Cite
|
Sign up to set email alerts
|

In Patients With Obesity, the Number of Adipose Tissue Mast Cells Is Significantly Lower in Subjects With Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is a rising global health problem mainly caused by obesity and a sedentary lifestyle. In healthy individuals, white adipose tissue (WAT) has a relevant homeostatic role in glucose metabolism, energy storage, and endocrine signaling. Mast cells contribute to these functions promoting WAT angiogenesis and adipogenesis. In patients with T2D, inflammation dramatically impacts WAT functioning, which results in the recruitment of several leukocytes, including monocytes, that enhance this inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…Here, we demonstrate that mast cells also undergo phenotypic changes in patients with T2D. In agreement with previous results of the group ( 27 , 44 ), in T2D, mast cells are more affected in o-WAT than in s-WAT. The decrease in the surface expression of CD117 in patients with T2D can explain the reduction in the number of mast cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, we demonstrate that mast cells also undergo phenotypic changes in patients with T2D. In agreement with previous results of the group ( 27 , 44 ), in T2D, mast cells are more affected in o-WAT than in s-WAT. The decrease in the surface expression of CD117 in patients with T2D can explain the reduction in the number of mast cells.…”
Section: Discussionsupporting
confidence: 93%
“…Once it was clear that mast cells are important players in metabolically healthy expansion and do not contribute to T2D we and others decided to investigate if T2D negatively affects mast cells. Previous studies of our group demonstrated that the number of mast cells decreases in patients with T2D, especially in o-WAT (27). Besides, we observed that after bariatric surgery, the number of mast cells increased 10-fold in o-WAT and 4-fold in s-WAT (44).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Mast cells are highly differentiated, widely distributed cells of the innate immune system. The involvement of mast cells in diabetes is corroborated by findings indicating that these cells are associated with inflamed adipose tissue, the development of certain diabetes complications such as diabetic nephropathy, and reduced wound healing in the case of diabetic foot lesions [70][71][72][73]. In the present review we have discussed the role of mast cells in the diabetic pancreas.…”
Section: Discussionsupporting
confidence: 54%
“…In healthy individuals, WAT plays an important role in metabolism and energy homeostasis throughout the body. However, people with obesity and type two diabetes (T2D) experience an inflammatory response in their adipose tissue, particularly in visceral white fat that contains higher levels of reactive oxidative species ( 29 , 31 ). WAT differentiation and cell functioning is primarily controlled by the peroxisome proliferator-activated receptor gamma (PPARγ), also known as the “master” regulator of adipogenesis ( 32 ).…”
Section: Adipogenesis Nuclear Receptors and Key Pathwaysmentioning
confidence: 99%